Ber-H2 (CD30) Immunohistochemical Staining of Human Fetal Tissues (International Journal of Biological Sciences, 2005)
OBJECTIVE: CD30 antigen has long been considered to be restricted to the tumour cells of Hodgkin's disease and of anaplastic large cell lymphoma as well as to T and B activated lymphocytes. It is now apparent that the range of normal and neoplastic cells, which may express CD30 antigen, is much wider than was at first thought. In order to gain insight into the physiological function of CD30 antigen, we studied the distribution of its expression in the tissues of fetuses from week 8th to week 16th. MATERIALS AND METHODS: We investigated the immunohistochemical expression of CD30 antigen in paraffin-embedded tissue samples representing all systems from 30 fetuses after therapeutic abortion at 8th to 10th and 12th to 16th week of gestation, respectively, using the monoclonal antibody Ber-H2. RESULTS: Our results demonstrated that CD30 is expressed early in human fetal development (8th to 10th week of gestation) in several fetal tissues derived from all three germ layers (gastrointestinal tract, special glands of the postpharyngeal foregut, urinary, musculoskeletal, reproductive, nervous, endocrine systems), with the exception of the skin and hematolymphoid system (thymus), in which the antigen is expressed later on (10th week onwards). Expression of CD30 was restricted to the hematolymphoid system in the 12-16 weeks of gestation. No expression of the marker was observed in the respiratory and cardiovascular systems during the entire period examined. CONCLUSIONS: CD30 antigen is of importance in cell development, and proliferation. It is also pathway-related to terminal differentiation in many fetal tissues and organs.